Toxoplasma gondii in milk of naturally infected dairy ewes on west mesoregion of Santa Catarina state, Brazil - Ossani R.A.* (2017)
This study aimed to detect Toxoplasma gondii in the milk of dairy sheep in the Western mesorregion of state of Santa Catarina by bioassay (22 milk samples from eight ewes seropositive; IFA ≥256) and PCR [for the detection of agent in the brains of mice inoculated on bioassay and directly from milk (108 samples from 42 seropositive ewes (IFA, ≥64) in different lactation periods)]. T. gondii DNA was detected in mice brains inoculated with milk from eight sheep (a sample of the 45th day of lactation and seven in the collection of 90th day) and directly from the milk in samples of the second collection (90 days) in five animals. Taking into account both assays, from a total of 42 ewes in lactation and seropositive for T. gondii, 30.95% (13/42) of the animals presented evidences of T. gondii presence in milk. Positive PCR samples were sequenced and the results confirmed ≥97% identity with the membrane antigen P22 gene of T. gondii. The results showed that T. gondii is present in the milk of sheep, representing a possible source of infection to humans through the consumption of milk "in natura" and/or derivatives, besides the possibility of lactogenic transmission to lambs.